Labour Market Characteristics of Helping Professionals - Csók, Cintia (Central European Journal of Educational Research, 2020)
In Hungary, considerable efforts have been made in recent years to analyse the career paths of higher educational graduates, which have highlighted the need for field-specific and training-specific analysis. In this context, our research concentrates on a special training segment, focusing on the position of young professionals working in occupations helping the function of the society. Previous research focused only on the professionalization of the different occupations and the recruitment was examined from institutional and regional aspects. However, during the statistical analysis we examined the social recruitment base and the labour market situation of social pedagogy graduates in the Graduates 2012 (Frissdiplomások 2012) national database. The novelty of our work lies in the comparison of those who graduated in social work, pedagogy and andragogy in full-time programs. The most important result of our quantitative analysis is the statement that the differences in the composition of the group are strongly explained by the regional location of the institutions providing the training. In terms of horizontal and vertical congruence, the values of the humanities group are the most unfavourable.